Geometric ring annuloplasty as an adjunct to aortic valve repair: clinical investigation of the HAART 300 device - Mazzitelli, Domenico; Fischlein, Theodor; Rankin, J Scott; Choi, Yeong-Hoon; Stamm, Christof; Pfeiffer, Steffen; Pirk, Jan; Detter, Christian; Kroll, Johannes; Beyersdorf, Friedhelm; Griffin, Charles D; Shrestha, Malakh; et al. (European journal of cardio-thoracic surgery, 2016)
OBJECTIVES: This study assessed the safety and efficacy of an internal geometric annuloplasty ring in a regulatory trial of aortic valve reconstruction (ClinicalTrials.gov Identifier: NCT01400841). METHODS: Sixty-five patients with predominant moderate-to-severe trileaflet aortic insufficiency (AI) underwent aortic valve repair with an average age of 63 ± 13 years (mean ± SD). All had initial implantation of an internal aortic annuloplasty ring to correct annular dilatation and facilitate leaflet reconstruction. Leaflet plication was performed for prolapse in 80% of patients, and more complex leaflet procedures, usually employing autologous pericardium, were required in 22%. Ascending aortic and/or root aneurysms were replaced in 62%. RESULTS: Follow-up was for a maximum of 3 years and a mean of 2 years. No in-hospital operative mortalities, major complications or early or late valve-related events occurred. The annular diameter before repair was 26.5 ± 2.3 mm, and the average ring diameter used was 21.5 ± 1.6 mm. The preoperative AI grade (0-4) was 2.9 ± 0.8 and improved after repair to 0.6 ± 0.7 (P < 0.0001), as did the NYHA class. The mean valve gradient was 8.6 ± 4.3 mmHg, and at 3 years, the Kaplan-Meier survival rate was 95%, with no valve-related mortality. Over the 3 years, aortic valve replacement was required in 7 patients (10.8%) for reasons usually related to surgical technique. Most repair failures occurred early, and results stabilized after 6 months. No structural complications of the rings were observed. CONCLUSIONS: Geometric ring annuloplasty was a safe and effective adjunct to aortic valve repair. Initial correction of annular dilatation seemed to facilitate overall reconstruction. Because most early repair failures were technical, increasing experience with geometric ring annuloplasty for aortic valve reconstruction has the potential to standardize and improve outcomes.
Keywords: dospělí; Cardiac Valve Annuloplasty; Female; aortální chlopeň; anuloplastika srdeční chlopně; Adult; ženské pohlaví; srdeční chlopně umělé; lidé; Heart Valve Prosthesis; aortální insuficience; Aortic Valve Insufficiency; Aged, 80 and over; Reoperation; reoperace; prospektivní studie; Male; Aged; Prospective Studies; Aortic Valve; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans